The collaborative economy in the specters of neoliberal capitalism - Rojas, Luis Suárez (2019)
This article explores the paradigm of collaborative economy, analyzing its possibledefinitions, limitations and contradictions of work in the contemporary world. In addition,we offer a contextual analysis of global forces and local impacts, based on life stories ofdriver-partners of the private transportation company Uber.